B2B COMPANIES GO ONLINE MARKET: TRENDS AND FORECAST - KHAZHENSKA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article describes the significant role of B2B online sales in e-commerce. The aim of the research was to determine whether it is worthwhile for B2B players to invest in online platforms. A market study was analyzed, revealing that the impact of B2B e-commerce on economic development has not been sufficiently explored. The issue of investing in B2B online platforms was examined. The labor market has been joined by a new generation of Z and Millennials, who occupy positions as procurement technical managers and seek all the necessary information online before making a purchase. They find it much more interesting to systematically gather all the required information than to make phone calls and engage in direct communication. The author presents statistical figures showing how the B2B market is developing in the top 10 leading countries and provides a detailed forecast for this niche. The forecast is based on the proven statistical data in the USA as 2nd place player in e-commerce in the world. The behavior of procurement managers was analyzed, indicating that the overwhelming majority prefer self-service over traditional communication methods, emphasizing the need for an online platform for B2B business. The market share of this segment in various top countries, investment shares, and the amount buyers are willing to spend online when making B2B purchases were also demonstrated. The paper discusses the structure of key indicators in B2B online sales. The author provides a deep analysis with individual recommendations on how to enter the B2B market. The main advantages of a B2B portal are shown, such as the presence of a personal account, the company’s online presence, the ability to place orders 24/7, as the market becomes global and buyers may be in different time zones, automation of all processes, avoidance of personal factors and errors, automatic invoicing and tracking of debts, integration with ERP and CRM (Customer Relationship Management) systems, and reduction of sales department costs. The author also highlights potential challenges that B2B players may face on this path. Steps to overcome bottlenecks and a marketing plan for promoting a B2B online platform are suggested. The business case of Caterpillar’s mobile application is presented as an example. Thus, as shown in the study, this niche offers significant and brilliant business prospects, and there is a reason to invest in it.